Diabetes in Patients With Heart Failure With Reduced Ejection Fraction During Hospitalization: A Retrospective Observational Study - Zhou, Yiling; Wang, Miye; Wang, Si; Li, Nan; Zhang, Shengzhao; Tang, Siqi; Shi, Qingyang; Zhao, Yuliang; Li, Jingwen; Zeng, Yuping; Song, Huan; Tian, Haoming; et al. (Frontiers in Endocrinology, 2021)
Background: Diabetes is prevalent worldwide including hospitalized patients with heart failure with reduced ejection fraction (HFrEF). This retrospective study investigated the association of diabetes with in-hospital adverse events in patients with HFrEF. Methods: We analyzed data from electronic medical records of patients hospitalized with HFrEF in West China Hospital of Sichuan University from January 1, 2011, to September 30, 2018. Propensity score matching balances the baseline characteristics between patients with and without diabetes. Logistic and Poisson regressions investigated the association of diabetes with risks of intubation, cardiogenic shock, acute kidney injury (AKI), intensive care unit (ICU) admission and death during hospitalization, and length of ICU and hospital stay in the matched cases. Results: Among 6,022 eligible patients (including 1,998 with diabetes), 1,930 patient pairs with and without diabetes were included by propensity score matching. Patients with diabetes had a significantly increased risk of intubation (odds ratio [OR], 2.69; 95% confidence interval [CI], 2.25–3.22; P<0.001), cardiogenic shock (OR, 2.01; 95% CI, 1.72–2.35; P<0.001), AKI at any stage (OR, 1.67; 95% CI, 1.44–1.94; P<0.001), ICU admission (OR, 1.89; 95% CI, 1.65–2.15; P<0.001), and death (OR, 4.25; 95% CI, 3.06–6.02; P<0.001) during hospitalization. Patients with diabetes had longer ICU (median difference, 1.47 days; 95% CI, 0.96–2.08; P<0.001) and hospital stay (2.20 days; 95% CI, 1.43–2.86; P<0.001) than those without diabetes. There were potential subgroup effects by age and by ischemic heart disease, hypertension, and CKD status on the association of diabetes with risk of AKI at any stage; and subgroup effects by sex and CKD status on the association of diabetes with risk of intubation. The increase in length of hospital stay was larger in patients without hypertension than those with hypertension. Conclusions: Among patients with HFrEF, those with diabetes have a worse prognosis, including a higher risk of in-hospital intubation, cardiogenic shock, AKI, ICU admission and death during hospitalization, and longer ICU and hospital stay.